The influence of coaches` instruction on technical actions, tactical behaviour, and external workload in football small-sided games - Batista, J.; Goncalves, B.; Sampaio, J.; Castro, J.; Abade, E.; Travassos, B. (Montenegrin Journal of Sports Science and Medicine, 2019)
This study aimed to explore the effects of previous instruction on technical, tactical and external workload performances in football small-sided games. Two 7-a-side balanced competitive teams received instructions regarding the rules of the small-sided games proposed. Additionally, one team received instructions from the coach regarding the collective tactical behaviour required for each exercise condition: (a) Without strategic instruction (WSI); (b) Defensive strategy (DS); (c) Offensive strategy (OS) to play against the team that only received the rules of the small-sided games. The comparisons among game scenarios were assessed via standardised mean differences. The comparison between WSI and DS revealed higher number of defensive actions, less space covered, and more distance covered in jogging for DS in comparison with WSI. The comparison between WSI and OS revealed more passes per ball possession, larger team length, larger space covered, lower distance covered walking, and more distance covered in jogging for OS in comparison with WSI. The results reinforce that coaches` previous instruction constrains the technical, tactical, and physical demands of small-sided games in football. The use of previous instruction regarding strategical and tactical behaviour allows highlighting the players` behaviour and ensures functional team performance.